Multi-Scale Kinetic Simulation of Magnetic Reconnection With Dynamically Adaptive Meshes - Fujimoto, Keizo (Frontiers in Physics, 2018)
Magnetic reconnection is essentially a multi-scale phenomenon, driven by kinetic process in microscopic region and enabling explosive energy conversion from magnetic field energy to plasma kinetic energy in large area. It has been poorly understood how the kinetic process around the x-line connects to the magnetohydrodynamics (MHD) scale process in the reconnection downstream region. The present study has investigated the energy conversion process in the region far downstream of the x-line, by means of the particle-in-cell (PIC) simulation with the adaptive mesh refinement (AMR). The AMR-PIC model enables efficient kinetic simulation of multi-scale phenomena using dynamically adaptive meshes. It is found that the ion energy gain dominates in the reconnection region and is carried out mainly in the exhaust center rather than the exhaust boundaries. The simulation results suggest that the energy conversion process in collisionless magnetic reconnection is significantly different from that in the MHD reconnection model in which most energy conversion occurs at slow mode shocks formed at the exhaust boundaries.